Kombinasi Digital Marketing, Marketing Konvensional Dalam Strategi Pemasaran Produk UMKM Di Kampung Cikandang - Wati Rahayu; Linda Novianti; Yuliani Istiqomah (Jurnal Inovasi Masyarakat, 2024)
Digital Marketing is product marketing through digital media, while conventional marketing uses traditional media such as print, television and radio. The majority of MSMEs in Cikandang Village choose to use these two promotional systems, especially for culinary products because they are considered more effective. This research was carried out using documentation data collection techniques with MSMEs in Kp. Cikandang Rw. 06 Etc. Cileunyi Kulon. The research results show that combining digital marketing and conventional marketing in product marketing strategies is effective in reaching a wider market. This combination has proven to be very effective for marketing products sustainably. MSME players can expand their marketing reach by combining two marketing systems, namely using various digital media such as Go Food, Grab Food, Shopee Food, Whatsapp and other platforms provided by business owners as part of marketing, and at the same time business owners can promote their products. with a direct marketing system (conventionally) with the aim of achieving a wider market share